2015
DOI: 10.1039/c5ra12099c
|View full text |Cite
|
Sign up to set email alerts
|

A simple and efficient synthesis of 9-arylfluorenes via metal-free reductive coupling of arylboronic acids and N-tosylhydrazones in situ

Abstract: A general, yet efficient synthesis of 9-arylfluorenes via metal-free reductive coupling of N-tosylhydrazones and arylboronic acids has been developed. This methodology is realized by a one-pot protocol in two steps involving the preparation of Ntosylhydrazones by reacting tosylhydrazide with 9-fluorenone derivatives, followed by the reductive coupling of arylboronic acid in the presence of potassium carbonate to afford various 9-arylfluorenes analogues in moderate to excellent yields. Importantly, the catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…[18] This metal-free approach also enabled the synthesis of 9fluorenyl-substituted carbazolyl derivatives in good yields.W hile expandingt he scope of this methodology,t he authors observed that the electronic and steric perturbations had as ignificant influence on the reaction outcome. [18] This metal-free approach also enabled the synthesis of 9fluorenyl-substituted carbazolyl derivatives in good yields.W hile expandingt he scope of this methodology,t he authors observed that the electronic and steric perturbations had as ignificant influence on the reaction outcome.…”
Section: Reductive Coupling With Boronic Acidsmentioning
confidence: 97%
“…[18] This metal-free approach also enabled the synthesis of 9fluorenyl-substituted carbazolyl derivatives in good yields.W hile expandingt he scope of this methodology,t he authors observed that the electronic and steric perturbations had as ignificant influence on the reaction outcome. [18] This metal-free approach also enabled the synthesis of 9fluorenyl-substituted carbazolyl derivatives in good yields.W hile expandingt he scope of this methodology,t he authors observed that the electronic and steric perturbations had as ignificant influence on the reaction outcome.…”
Section: Reductive Coupling With Boronic Acidsmentioning
confidence: 97%
“…[35] Thus using 9-fluorenones as the starting materials, the different hydrazones were produced on treatment with tosyl hydrazide which was then coupled with arylboronic acids in the presence of a base to give the 9-arylfluorenes in high yields. [35] Thus using 9-fluorenones as the starting materials, the different hydrazones were produced on treatment with tosyl hydrazide which was then coupled with arylboronic acids in the presence of a base to give the 9-arylfluorenes in high yields.…”
Section: Metal Free Cross Coupling Protocolmentioning
confidence: 99%
“…A metal free one pot cross-coupling protocol for the synthesis of 9-arylfluorenes was reported by Liu and co-workers (Scheme 8). [35] Thus using 9-fluorenones as the starting materials, the different hydrazones were produced on treatment with tosyl hydrazide which was then coupled with arylboronic acids in the presence of a base to give the 9-arylfluorenes in high yields. This protocol could be extended further for the synthesis of 9-fluorenyl carbazolyl, which has a wide variety of applications in the material science.…”
Section: Metal Free Cross Coupling Protocolmentioning
confidence: 99%
“…[8] In 2015, Liu group reported a simple and efficient synthesis of 9-arylfluorenes via metal-free reductive coupling of arylboronic acids and Ntosylhydrazones. [9] Styrenes are versatile building blocks in organic synthesis. A number of functionalizations of styrenes such as hydroformylations, [10] amination, [11] oxidative cleavage [12] et.…”
Section: Introductionmentioning
confidence: 99%